Inclusive Education: A Qualitative Exploration in Greece and Cyprus - Ioannidi, Vasiliki (Progress in Language, Literature and Education Research Vol. 6, 2024)
Aim: Inclusive education has developed and established itself as a field of educational research and pedagogical practice in Higher Education. This chapter explores how university students–teachers perceive the skills of inclusive teachers in Greece and Cyprus. The main idea of the present research is an empirical investigation regarding inclusive teacher’s skills. Study Design: The research is based on the interpretative epistemological approach and on the principles of qualitative methodological design. Place and Duration of Study: Two focus groups of participants with experience in different educational contexts took part in the digital context of Higher Education, Greece and Cyprus, during the academic year 2022-2023. Methods: The data were collected based on free-writing texts in an e-learning environment. The free-writing texts were subjected to content analysis. The free-writing texts were anonymous. Results: The results show that the dominant view of the participants concerning the inclusive teacher focuses on collaborative, creative, communicative and moral dimensions. The application of inclusion is determined by the pedagogical practice and the main characteristics of the inclusive teacher. Conclusion: Conclusions cannot be generalized. However, this kind of knowledge can used within an understanding of the inclusive educational praxis and in supporting teachers’ -digital and pedagogical- competencies and personal/professional development. The teachers’ skills in inclusive learning environments can contribute to a more inclusive educational landscape in Greece and Cyprus, fostering and ensuring the well-being of all students with and without specials educational needs.